The genomic landscape of pediatric renal cell carcinomas - Beck, Pengbo; Selle, Barbara; Madenach, Lukas; Jones, David T. W.; Vokuhl, Christian; Gopisetty, Apurva; Nabbi, Arash; Brecht, Ines B.; Ebinger, Martin; Wegert, Jenny; Graf, Norbert; Gessler, Manfred; et al. (iScience, 2022)
Pediatric renal cell carcinomas (RCC) differ from their adult counterparts not only in histologic subtypes but also in clinical characteristics and outcome. However, the underlying biology is still largely unclear. For this reason, we performed whole-exome and transcriptome sequencing analyses on a cohort of 25 pediatric RCC patients with various histologic subtypes, including 10 MiT family translocation (MiT) and 10 papillary RCCs. In this cohort of pediatric RCC, we find only limited genomic overlap with adult RCC, even within the same histologic subtype. Recurrent somatic mutations in genes not previously reported in RCC were detected, such as in CCDC168, PLEKHA1, VWF, and MAP3K9. Our papillary pediatric RCCs, which represent the largest cohort to date with comprehensive molecular profiling in this age group, appeared as a distinct genomic subtype differing in terms of gene mutations and gene expression patterns not only from MiT-RCC but also from their adult counterparts.
Gesehen am 31.05.2022